(untitled) (Journal of Face Aesthetics, 2021)
Aesthetic medicine is very popular among women and men as a tool to improve the external appearance, thereby increasing self-confidence and facilitating interpersonal contacts. No need for post-procedures convalescence, low invasiveness and documented effects make skin peels one of the most-chosen procedures offered by cosmetology and aesthetic medicine surgeries. Due to their variety and simplicity of the procedure, some of them can be successfully used at home. They allow to improve the overall condition of the skin – smoothing out superficial wrinkles, skin colour improvement, increase tension of the skin. Positive effects are noted not only by clinicians, but also by persons undergoing facial skin peels, as presented in the own study.